The role of repairing lung lacerations during video-assisted thoracoscopic surgery evacuations for retained haemothorax caused by blunt chest trauma - Chou, Yi-Pin; Kuo, Liang-Chi; Soo, Kwan-Ming; Tarng, Yih-Wen; Chiang, Hsin-I.; Huang, Fong-Dee; Lin, Hsing-Lin (European journal of cardio-thoracic surgery, 2014)
OBJECTIVES Retained haemothorax and pneumothorax are the most common complications after blunt chest traumas. Lung lacerations derived from fractures of the ribs are usually found in these patients. Video-assisted thoracoscopic surgery (VATS) is usually used as a routine procedure in the treatment of retained pleural collections. The objective of this study was to find out if there is any advantage in adding the procedure for repairing lacerated lungs during VATS. METHODS Patients who were brought to our hospital with blunt chest trauma were enrolled into this prospective cohort study from January 2004 to December 2011. All enrolled patients had rib fractures with type III lung lacerations diagnosed by CT scans. They sustained retained pleural collections and surgical drainage was indicated. On one group, only evacuation procedure by VATS was performed. On the other group, not only evacuations but also repair of lung injuries were performed. Patients with penetrating injury or blunt injury with massive bleeding, that required emergency thoracotomy, were excluded from the study, in addition to those with cardiovascular or oesophageal injuries. RESULTS During the study period, 88 patients who underwent thoracoscopy were enrolled. Among them, 43 patients undergoing the simple thoracoscopic evacuation method were stratified into Group 1. The remaining 45 patients who underwent thoracoscopic evacuation combined with resection of lung lacerations were stratified into Group 2. The rates of post-traumatic infection were higher in Group 1. The durations of chest-tube drainage and ventilator usage were shorter in Group 2, as were the lengths of patient intensive care unit stay and hospital stay. CONCLUSIONS When compared with simple thoracoscopic evacuation methods, repair and resection of the injured lungs combined may result in better clinical outcomes in patients who sustained blunt chest injuries.